Efecto y momento oportuno en la aplicación de diferentes dosis de Carburo de Calcio como Inductor Floral, en el cultivo de Piña (Annanas Comosus) Cultivar Golden Md-2 En Lamas - Montenegro Goicochea, Ausver (2010)
This paper titled “Effect and timing in the application of differents doses of calcium carbide floral induction in pineapple (Annan comosus) cultivar Golden MD-2 in Lamas” was held in the jurisdiction of the district Lamas, Jula sector, Lauezzari fundo, in order to determine the optimal dose and age with the application of calcium carbide as a floral inducer. This study was a block design d with factorial arrangement of 3 x 3 with 9 treatments, three replications and 20 seedlings per treatment. The doses used were 2, 3 and 4 grams per liter of calcium carbide d floral induction, the same was applied in 8, 9 and 10 months of age. The results obtained indicate that a 100% flowering at 60 days using a dose of 3 g/l calcium carbide floral induction in cultivar Golden MD-2 and age of application of calcium carbide was at10 months, earning 100% of the floral induction.